2020
DOI: 10.1200/cci.18.00095
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Sequential Treatments in Metastatic Breast Cancer

Abstract: PURPOSE Treatment sequencing of metastatic breast cancer (MBC) is heterogeneous. The primary objective of this study was to develop a visualization technique to understand population-level treatment sequencing for MBC. Secondary outcomes were to describe the heterogeneity of MBC treatment sequencing, as measured by the proportion of patients with a rare sequence, and to generate hypotheses about the impact of sequencing on overall survival. METHODS This retrospective review evaluated treatment sequencing for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…35 In addition to treatment guidelines, tumor types, and prior treatments, insurance coverage, patient preferences, and the integration of a physician's personal experience with current scientific literature also influence treatment choices. [35][36][37][38] Tools are in development to rank the increasing number of regimens, such as the recently developed information theoretic network metaanalysis that was used to longitudinally rank HR-positive and ERBB2-negative treatments by efficacy. 39 We found a large variety in drug regimens used at a line and yearly level by subgroup, with some regimens being particularly infrequent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition to treatment guidelines, tumor types, and prior treatments, insurance coverage, patient preferences, and the integration of a physician's personal experience with current scientific literature also influence treatment choices. [35][36][37][38] Tools are in development to rank the increasing number of regimens, such as the recently developed information theoretic network metaanalysis that was used to longitudinally rank HR-positive and ERBB2-negative treatments by efficacy. 39 We found a large variety in drug regimens used at a line and yearly level by subgroup, with some regimens being particularly infrequent.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from the linked SEER and Medicare database found that 56% of patients received an overall treatment sequence that less than 11 other patients also received. 35 In addition to treatment guidelines, tumor types, and prior treatments, insurance coverage, patient preferences, and the integration of a physician’s personal experience with current scientific literature also influence treatment choices. 35 , 36 , 37 , 38 Tools are in development to rank the increasing number of regimens, such as the recently developed information theoretic network meta-analysis that was used to longitudinally rank HR-positive and ERBB2-negative treatments by efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an analysis of the large real-world US SEER-Medicare database investigated treatment sequences in 6639 patients with metastatic breast cancer (MBC). 33 The heterogeneity of sequencing in real life was illustrated by their finding that 56% of these patients received a sequence that fewer than 11 other patients received. 33 This makes it challenging to extrapolate the results of RCTs with defined sequencing to the real world.…”
Section: Methodsmentioning
confidence: 99%
“… 33 The heterogeneity of sequencing in real life was illustrated by their finding that 56% of these patients received a sequence that fewer than 11 other patients received. 33 This makes it challenging to extrapolate the results of RCTs with defined sequencing to the real world. RWE can help clinicians and regulators effectively conceptualize treatment patterns and patient outcomes, improving patient care in oncology.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of LOT data from real-world transactional claims and electronic health records (EHRs) is essential for determining longitudinal SACT changes in real-world clinical care settings, but it is challenging because LOT information is often not clearly marked in structured data sets and therefore must be interpreted through clinical notes [6,9]. Researchers and clinicians use LOT information gathered retrospectively to determine the effectiveness of SACT regimens, identify trends in clinical practice patterns, identify eligible candidates for cancer trials, and conduct quality assurance to help ensure that patients receive optimal SACT [6,10,11]. Manual determination of LOT information for large numbers of patients is time consuming and often not feasible, prompting our own and others' searches for automated LOT algorithmic methods [6,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%